2000
DOI: 10.1096/fj.00-0414fje
|View full text |Cite
|
Sign up to set email alerts
|

The common Arg 972 polymorphism in insulin receptor substrate‐1 causes apoptosis of human pancreatic islets

Abstract: Molecular scanning of human IRS-1 gene revealed a common polymorphism causing Gly-->Arg972 change. Diabetic and pre-diabetic carriers of Arg972 IRS-1 are characterized by low fasting levels of insulin and C-peptide. To investigate directly whether the Arg 972 IRS-1 affects human islet cells survival, we took advantage of the unique opportunity to analyze pancreatic islets isolated from three donors heterozygous for the Arg972 and six donors carrying wild-type IRS-1. Islets from carriers of Arg972 IRS-1 showed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
65
0
1

Year Published

2001
2001
2024
2024

Publication Types

Select...
6
2
1

Relationship

4
5

Authors

Journals

citations
Cited by 86 publications
(69 citation statements)
references
References 41 publications
3
65
0
1
Order By: Relevance
“…Phosphorylation of Bad provides an important link between extracellular survival factors and the intrinsic cell death pathway. The primary role of 14-3-3 proteins is to inhibit apoptosis; they bind to phosphorylated Bad, which prevents the formation of the Bad⅐Bcl-xL complex (35). Phosphorylation of different residues of the Bad proteins appears to have distinct consequences.…”
Section: Discussionmentioning
confidence: 99%
“…Phosphorylation of Bad provides an important link between extracellular survival factors and the intrinsic cell death pathway. The primary role of 14-3-3 proteins is to inhibit apoptosis; they bind to phosphorylated Bad, which prevents the formation of the Bad⅐Bcl-xL complex (35). Phosphorylation of different residues of the Bad proteins appears to have distinct consequences.…”
Section: Discussionmentioning
confidence: 99%
“…16 -20 Thus, it has been demonstrated that the presence of the Gly3 Arg change at codon 972-IRS-1 causes a specific defect in binding of the p85 regulatory subunit of PI3-K to the IRS-1 variant. 16,20 This results in a decrease in IRS-1-associated PI3-K activity and in the subsequent reduced activation of the Ser/Thr kinase-Akt, a key enzyme linking PI3-K activation to multiple biological functions of insulin, including glucose transport, glycogen synthesis, and eNOS activation. [17][18][19][20] In HUVECs naturally expressing the G972R-IRS-1 variant, we observed cell-specific impairment of insulin action, as revealed by defective insulin-stimulated eNOS activation and expression.…”
Section: Discussionmentioning
confidence: 99%
“…16,20 This results in a decrease in IRS-1-associated PI3-K activity and in the subsequent reduced activation of the Ser/Thr kinase-Akt, a key enzyme linking PI3-K activation to multiple biological functions of insulin, including glucose transport, glycogen synthesis, and eNOS activation. [17][18][19][20] In HUVECs naturally expressing the G972R-IRS-1 variant, we observed cell-specific impairment of insulin action, as revealed by defective insulin-stimulated eNOS activation and expression. Indeed, we observed that in the cells carrying the G972R-IRS-1 variant, the IRS-1/PI3-K/PDK-1/protein kinase B/Akt insulin-signaling cascade was impaired (as documented by reduced IRS-1-associated PI3K activity and reduced insulin-stimulated Akt phosphorylation), whereas MAPK pathway activity was increased.…”
Section: Discussionmentioning
confidence: 99%
“…12 Insulin can prevent pancreatic b cell apoptotic death through the involvement of sequential induction of IRS-1-associated PI 3-kinase activity, Akt activity, and Bad phosphorylation at Ser-112 and Ser-136. 13 On occasion, Bad up-regulation has been reported to lead to cell death as a result of drug treatment. 14 The infectious pancreatic necrosis virus (IPNV) is a fishderived pathogen and is the prototype of the Birnaviridae virus family.…”
Section: Introductionmentioning
confidence: 99%